The Empire State Building : The Making of a Landmark - Tauranac, John, 1939- (Book collections on Project MUSE., 2014)
The Empire State Building is the landmark book on one of the world's most notable landmarks. Since its publication in 1995, John Tauranac's book, focused on the inception and construction of the building, has stood as the most comprehensive account of the structure. Moreover, it is far more than a work in architectural history; Tauranac tells a larger story of the politics of urban development in and through the interwar years. In a new epilogue to the Cornell edition, Tauranac highlights the continuing resonance and influence of the Empire State Building in the rapidly changing post-9/11 cityscape.